Pariwisata Berbasis Komunitas: Menciptakan Nilai Baru pada Lanskap Budaya dengan Kebangkitan Pariwisata Lokal Melalui Toko Buku Independen di Korea - Setyaningsih, Nining; Latifah, Eva (East Asian Review, 2023)
This research explores the phenomenon of community-based content tourism in Korea as a manifestation of localism, cultural innovation and social activism. Focusing on citizen cultural space tourism on Jeju Island, this study provides an examination of how independent bookstores driven by Jeju Island locals have become innovative catalysts for promoting unique cultural experiences and fostering a sense of community engagement in the tourism ecosystem. The study highlights the role of independent bookstores in revitalizing local culture, promoting reading, and attracting tourists. By analyzing the cases, this study highlights the potential of independent bookstores as agents of cultural landscape transformation and form. Furthermore, this research is expected to contribute to providing new knowledge on ways to increase tourism attraction in a region.